Contributing factors of labor productivity in the industrial sector in Indonesia: a comparative study among regions - Muhammad Amir Arham; Stella Junus (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
TIndonesia’s degree of competitiveness in attracting investment is relatively low compared to other ASEAN countries, e.g., Singapore, Malaysia, Thailand, and Vietnam, despite the country’s potential resources. Specifically, low labour productivity in industrial sector led to lower degree of investment competitiveness in Indonesia. Thus, this study aims to examine the transformation of economic structures and factors determining the regional labor productivity in industrial sector in Indonesia. This study employs multiple regression method with panel data approach on 34 provinces in Indonesia from 2014 to 2019. This study suggests that, in general, the decline of agriculture sector share in the Eastern part of Indonesia was greater than the Western part of Indonesia. Furthermore, the composition of labor absorption in Sulawesi, Maluku, Papua, and Kalimantan decline periodically. This research also suggests that the factors leading to improvement of productivity in the Industrial sector in Western part of Indonesia is real wages. Moreover, provision of electricity is the contributing factor and hampers labor productivity in the Eastern part of Indonesia. This study further concluded that supply of electricity is substitutional to labor which result in the decline of productivity